Pendekatan Nilai-Nilai Kearifan Lokal dalam Pembelajaran Pendidikan Kewarganegaraan sebagai Penguatan Karakter - Jamaludin Jamaludin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study is to explore the values of local wisdom as an approach to civic education learning content in the global era in strengthening national character in the Department of Pancasila and Citizenship Education, Faculty of Social Sciences, State University of Medan, the focus of the problem in this research is efforts to strengthen national character built through learning content by exploring the values of local wisdom so that it becomes a strong foundation to become a citizen with a global perspective. The theory used integrates the concepts that exist on the basis of character values, namely Spiritual and Emotional Development, intellectual development, sports/kinesthetic physical and kinesthetic development and Affective and creativity development feelings/intentions that have been combined with values. - the value of local wisdom. This type of research is qualitative to describe the values of local wisdom as an effort to approach the content of civic education learning. Data were obtained through observation, interviews, FGD (focus group discussions) and documentation studies. The data were analyzed using the data analysis technique proposed by Miles and Hubermen which consisted of three activity lines, namely data reduction, data presentation and conclusion drawing. The results and conclusions of this study indicate that the content of Citizenship learning based on local wisdom with global insight and national character that was developed is very appropriate and suitable to be used for citizenship education courses as core courses in the Department of Pancasila and Citizenship Education, Faculty of Social Sciences, State University of Medan. Another finding shows that Civics learning based on local wisdom with a global perspective can strengthen the values of national character among students in the scope of life in the global era.